2011
DOI: 10.1007/s10764-011-9506-y
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Contributions to Hylobatid Taxonomy and Adaptation

Abstract: Compared with the great apes, the small-bodied hylobatids were treated historically as a relatively uniform group with 2 genera, Hylobates and the larger-bodied Symphalangus. Four genera are now recognized, each with a different chromosome number: Hoolock (hoolock) (38), Hylobates (44), Nomascus (crested gibbon) (52), and Symphalangus (siamang) (50). Previous morphological studies based on relative bone lengths, e.g., intermembral indices; molar tooth sizes; and body masses did not distinguish the 4 genera fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Orangutans do not resemble the African apes; they show correspondences with the siamang in having heavier forelimbs than hindlimbs, but curiously, not the gibbons (Hylobates) (Schultz, 1933;Zihlman et al, 2011). Overall, the orangutan hind limb is unique among catarrhine primates in its extreme flexibility and in the mass and length of the foot that extends its reach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Orangutans do not resemble the African apes; they show correspondences with the siamang in having heavier forelimbs than hindlimbs, but curiously, not the gibbons (Hylobates) (Schultz, 1933;Zihlman et al, 2011). Overall, the orangutan hind limb is unique among catarrhine primates in its extreme flexibility and in the mass and length of the foot that extends its reach.…”
Section: Discussionmentioning
confidence: 99%
“…For example, addition of segment mass for comparison to linear dimensions of ape fossils can take the evidence beyond an exclusive dependence on osteology and expand potential interpretations. Furthermore, application of soft tissue data can serve as another line of evidence along with molecular, dental-cranial, and skeletal to contribute to phylogeny (Pilbeam, 2000;Gibbs et al, 2000Gibbs et al, , 2002Zihlman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mean of 6 wild-shot males was 7.27 kg ± 0.44 SD and mean of 2 wild-shot females was 7.65 ± 0.21 kg (Geissmann 1993). However, in captivity mass may be larger (e.g., a 9.5-kg female- Zihlman et al 2011). In N. siki and N concotor males had slightly larger body masses than females, suggesting that the apparently smaller body masses in males of N. /eucogenys were due to variation in a small sample size.…”
Section: General Charactersmentioning
confidence: 95%
“…Shoulder joints are always flexed during takeoff (Channon et al 2010). Zihlman (2011) found that N. leueogenys has the heaviest body and limb proportions among the Hylobatidae (other genera of Nomascus were not included in the analysis), suggesting greater power in shoulder, hip, and knee motions. These capabilities allow N. leueogenys to "progress, like gymnasts, by means of their long and powerful arms, and throw themselves from one branch to another for distances of thirty feet and more" (Delacour 1933:72).…”
Section: Form and Functionmentioning
confidence: 98%